Identification of Putative Genes Involved in Limonoids Biosynthesis in Citrus by Comparative Transcriptomic Analysis - Wang, Fusheng; Wang, Mei; Liu, Xiaona; Xu, Yuanyuan; Zhu, Shiping; Shen, Wanxia; Zhao, Xiaochun (Frontiers in Plant Science, 2017)
Limonoids produced by citrus are a group of highly bioactive secondary metabolites which provide health benefits for humans. Currently there is a lack of information derived from research on the genetic mechanisms controlling the biosynthesis of limonoids, which has limited the improvement of citrus for high production of limonoids. In this study, the transcriptome sequences of leaves, phloems and seeds of pummelo (Citrus grandis (L.) Osbeck) at different development stages with variances in limonoids contents were used for digital gene expression profiling (DGE) analysis in order to identify the genes corresponding to the biosynthesis of limonoids. Pair-wise comparison of transcriptional profiles between different tissues identified 924 differentially expressed genes commonly shared between them. Expression pattern analysis suggested that 382 genes from three conjunctive groups of K-means clustering could be possibly related to the biosynthesis of limonoids. Correlation analysis with the samples from different genotypes, and different developing tissues of the citrus revealed that the expression of 15 candidate genes were highly correlated with the contents of limonoids. Among them, the cytochrome P450s (CYP450s) and transcriptional factor MYB demonstrated significantly high correlation coefficients, which indicated the importance of those genes on the biosynthesis of limonoids. CiOSC gene encoding the critical enzyme oxidosqualene cyclase (OSC) for biosynthesis of the precursor of triterpene scaffolds was found positively corresponding to the accumulation of limonoids during the development of seeds. Suppressing the expression of CiOSC with VIGS (Virus-induced gene silencing) demonstrated that the level of gene silencing was significantly correlated to the reduction of limonoids contents. The results indicated that the CiOSC gene plays a pivotal role in biosynthesis of limonoids.